Developing Online Learning Application for Programming Language - Ciptayani, Putu Indah; Saptarini, Ni Gusti Ayu Putu Harry; Hidayat, Reza Akbar; Dewi, Kadek Cahya (Universitas Negeri Malang, 2020)
.Online learning is one of the most practical and promising learning alternatives nowadays. Flexible time and low cost of online learning are advantages that offline learning does not have. In addition, in online learning, each student can enrol the material according to their level, interest and abilities.Â This study aims to build an online learning application for programming language. The method used in this study was Scrum software development. Scrum is one of the Agile method in software development. The system design using use case diagram resulted 3 actors and 8 use cases. The product backlog resulted in this study was five backlogs. The sprint composed based on product backlog result 4 sprints in total 120 daysâ€™ work. All five product backlogs were built successfully using Scrum. This system can be an alternative in learning programming language that offers the flexibility to the student, based on their ability and time.